Evaluation of Antibiotic Prescribing Practices and Antimicrobial Sensitivity Patterns in Urinary Tract Related Infectious Diseases in Pediatric Patients - Alavudeen, Sirajudeen S.; Asiri, Anas Ali; Fageeh, Shatha Abdulrahman; Aljarie, Ahmed Abdoh; Iqbal, Mir Javid; Khan, Noohu Abdulla; Tabassum, Fauzia; Rahamathulla, Mohamed; Hani, Umme; Akhtar, Md Sayeed (Frontiers in Pediatrics, 2021)
Complications of urinary tract infections (UTIs) like kidney failure and septicaemia develops once infections spread from the lower urinary tract to other parts of the body and it poses a great health and economic burden to the countries. This retrospective study was conducted among 132 patients with bacterial UTIs in the inpatient department of tertiary care hospital in Abha, Saudi Arabia. During the study period, Escherichia coli (E. Coli) and Klebsiella pneumonia (K. pneumonia) along with other 15 different bacteria were isolated. A significant difference (P<0.05) was observed between the male and female children population in different age groups. We observed fever (84.09 %) as a major symptom (P<0.05) and seizure (9 %) was reported as a major concomitant condition among UTI cases. Around 31.82 % of E. coli was found to be the most common uropathogens in paediatric cases followed by25 % in K. pneumoniae. E. coli was observed to be more susceptible (92.86 %) to amikacin, ceftriaxone, levofloxacin, ertapenem, gentamycin, meropenem, piperacillin-tazobactam, tigecycline and ceftazidime. However, meropenem, tigecycline and amikacin was observed to be effective in 100 % cases of K. pneumoniae. Meanwhile, cephalosporins were most commonly prescribed drug category among different classes of drugs. Almost 99 % paediatric cases, based on their age, were admitted in the ward and drugs were administered intravenously. We concluded that microbiology laboratory evidence on the causative organisms and choice of treatment together allows to tailor appropriate treatment regimen in conjunction with clinical experiences.